Software project management in practice - Jalote, Pankaj (Indianapolis, IN Pearson Education, Inc., 2002)
With an actual software project from Infosys used as a running example, the author explains the key aspects of successful project management-from process planning through project monitoring and closure. The practices discussed are also compatible with the widely adopted Capability Maturity Model® (CMM®). In the end, readers will gain a practical framework for systematically improving the planning and execution of any software project.
Includes bibliographical references and index
Keywords: Công nghệ thông tin